Identification of risk factors of computer information technologies in education. - Hrebniak, M. P.; Shchudro, S. A.; Yakimova, K. O. (Medicni Perspektivi, 2014)
The basic direction of development of secondary school and vocational training is computer training of schoolchildren and students, including distance forms of education and widespread usage of world information systems. The purpose of the work is to determine risk factors for schoolchildren and students, when using modern information and computer technologies. Results of researches allowed to establish dynamics of formation of skills using computer information technologies in education and characteristics of mental ability among schoolchildren and students during training in high school. Common risk factors, while operating CIT, are: intensification and formalization of intellectual activity, adverse ergonomic parameters, unfavorable working posture, excess of hygiene standards by chemical and physical characteristics. The priority preventive directions in applying computer information technology in education are: improvement of optimal visual parameters of activity, rationalization of ergonomic parameters, minimizing of adverse effects of chemical and physical conditions, rationalization of work and rest activity.